Décoloniser la vulnérabilité : penser l’agir minoritaire des femmes d’Afrique subsaharienne dans la cause du VIH en France - Marjorie Gerbier-Aublanc (Genre, Sexualité et Société)
Deeply affected by HIV in France, Sub-Saharan African women have been thought of as a “vulnerable group”, portrayed from the homogeneous category of “third world woman” victim of men in the epidemic. Based on an empirical analysis of their mobilization in the HIV cause, this paper aims at “decolonizing the vulnerability” they are supposed to embody, by unveiling the plural forms of agency they array in this field. The activities carried out within these women’s associations rest on a grammar of care which, by answering the material needs of the women and by acknowledging their capabilities, activate a “minority agency” process: set of tactics that they imagine, from their minority position, in order to negotiate the social positions assigned to them in France. Thus, the HIV cause appears as an area where acting as a “vulnerable being” becomes the driving force of political transformation.